Essays on African-American history, culture and society (U.S. Department of State, 2005)
This book, An African-American Reader, by educating readers throughout the world about the African American community and its history, can serve the cause of international understanding, for it offers an opportunity for those outside the United States whose understading of the African-American community is too often a metter of headlines to penetrate more depply into our history and to reflect on its depth and its complexity.